2018
DOI: 10.5993/ajhb.42.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Trust towards Physicians among Patients from 12 Hospitals in China

Abstract: Objective We investigated the level of physician trust in China and how it is influenced by various demographic factors. MethodsWe surveyed 12 public hospitals from which inpatients were randomly selected using hospitalization ID and outpatients were selected using census sampling to participate in the interview. Trust in physicians was measured using the Chinese version of Wake Forest Physician Trust Scale. Mixed-effects and logistic models were employed to study correlates of trust. ResultsThe distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…Few studies have discussed whether it could be a moderator. In China, in the context of unbalanced medical resource distribution and distrust between doctors and patients, this construct could play a more complicated role [66,68,80]. Our finding confirmed that this construct is a moderator, as trust had a significant moderation effect (beta=–.095; P =.049) on the path from PU to IU.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Few studies have discussed whether it could be a moderator. In China, in the context of unbalanced medical resource distribution and distrust between doctors and patients, this construct could play a more complicated role [66,68,80]. Our finding confirmed that this construct is a moderator, as trust had a significant moderation effect (beta=–.095; P =.049) on the path from PU to IU.…”
Section: Discussionsupporting
confidence: 74%
“…In China, patients’ trust of physicians is lower than in Western countries [66] and has become a serious social problem [67,68]. Trust in applied AI is an evolving phenomenon, and cognitive compatibility, trialability, and usability are the main factors related to trust in a technology [63].…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables were patients' opinions on healthcare quality, patient-provider interpersonal trust, and general life attitudes. This survey used the existing composite measures adapted from the Interpersonal Trust Scale (ITS) [23], Wake Forest Physician Trust Scale (WFPTS) [24] and SERVQUAL (Service Quality Scale) [25], to evaluate the quality of care [26] and patient-physician trust [27,28]. We also developed specific questions on participants' attitudes towards their life and health.…”
Section: Study Variablesmentioning
confidence: 99%
“…A survey indicated that in 2010 alone, there were over 17,000 cases of violence against doctors in China [ 60 ]. Patients tend to think that doctors put making money before patients’ health [ 61 ]. The negative consequence of distrust in doctors is that patients’ refusal to follow physicians’ clinical treatment comes at the cost of health deterioration.…”
Section: Discussionmentioning
confidence: 99%